Physicochemical Characterization and Evaluation of Seasonal Variations of Landfill Leachate and Groundwater Quality around Tanjaro Open Dump Area of Sulaymaniyah City, Kurdistan, Iraq - Sozan W. Rashid; Dler M. S. Shwan; Khsraw A. Rashid (Journal of Chemistry)
The current study is concerned with the primary environmental assessment of the physicochemical characterization of seasonal fluctuations in the leachate of Tanjaro open dump site in Sulaymaniyah City, and its impact on the quality of the groundwater. The primary characteristics of the leachates were their high levels of organic and inorganic components and their toxicity because of the presence of heavy metal concentrations. For almost all physicochemical parameters, the leachate from the Tanjaro area dumping has incredibly high values. All heavy metals were present in leachate, with the exception of cadmium and mercury, albeit at levels below their respective permitted limits. The characterization revealed that Leachate 1 (L1) may be referred to as young leachate, whereas Leachate 2 (L2) and Leachate 3 (L3) can be referred to as old leachate due to their pH values. It was indicated that the Tanjaro dumping is operating and in the early stages of stabilization. BOD5/COD was around 0.63, and the leachate was highly biodegradable in the anaerobic phase. Groundwater, which contains little to no organic matter, was not found to be severely affected by monitoring wells located close to the dumpsites. The conductivity, total dissolved solids, total hardness, Mn, and Fe were some of the values that went above the WHO guidelines. Correlation analysis was used as a preliminary descriptive technique to establish the strength of the association between the relevant variables. Some parameters were discovered to be statistically significantly correlated with one another, pointing to a close connection between these parameters.